A covalent triazine nanosheet loaded with metal atoms and its preparation method and application
By preparing highly crystalline covalent triazine framework nanosheet carriers rich in carboxyl groups, the problem of easy agglomeration and uneven distribution of metal single atoms in covalent triazine framework materials was solved, the efficient utilization and uniform distribution of metal single atoms were achieved, and the electrocatalytic performance and stability of the catalyst were improved.
Patent Information
- Application Number
- CN202510990159.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-07-18
AI Technical Summary
Existing covalent triazine framework materials have problems such as easy agglomeration of single atoms, limited loading capacity, uneven distribution, unclear catalytic mechanism and difficulty in regulating electronic structure in loaded metal single atom catalysts, which affect their application in zinc-air batteries and other fields.
Synthesized highly crystalline, carboxyl-rich covalent triazine framework nanosheets are used as carriers. The electronic structure of metal single atoms is regulated by small molecule coordination to ensure their uniform dispersion and stable loading, and electronic effector groups are used to improve catalytic activity.
The efficient utilization and uniform distribution of metal single atoms are achieved, which significantly improves the catalytic performance, especially in the electrocatalytic oxygen evolution reaction, showing excellent catalytic effect and maintaining good physical and chemical stability.
Smart Images

Figure CN120532546B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of porous organic polymers, and in particular relates to a covalent triazine nanosheet loaded with metal atoms and a preparation method and application thereof. Background Art
[0002] Take zinc-air batteries, for example. This technology is considered a key development direction in the future of energy storage. Zinc-air batteries, characterized by high energy density, low cost, and environmental friendliness, have become a hot topic of research. However, practical applications of zinc-air batteries still face challenges in cycling stability, energy conversion efficiency, and electrode reaction kinetics. These issues directly impact the practical application and commercialization of zinc-air batteries. OER is a key electrochemical reaction in zinc-air batteries. Its relatively slow kinetics have become a bottleneck limiting battery performance. Therefore, developing efficient electrocatalysts to accelerate the OER reaction has become crucial for improving the overall performance of zinc-air batteries. Nanoporous materials, as effective supports for electrocatalysts, have attracted considerable attention in recent years. Nanoporous materials possess exceptionally large surface areas and unique pore structures, providing numerous active sites during loading and reaction processes. Covalent organic frameworks and metal-organic frameworks are two prominent categories, whose unique two-dimensional structures hold great promise for electrocatalytic applications.
[0003] For example, metal single-atom catalysts (SACs) supported on crystalline porous organic materials have attracted widespread attention due to their cyclically ordered structures, efficient atom utilization, rapid transport capabilities, and excellent electrocatalytic performance. They have been widely applied in oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), oxygen evolution reaction (OER), nitrogen reduction reaction (NRR), and carbon dioxide reduction reaction. Covalent triazine frameworks (CTFs), as a member of crystalline porous organic framework materials, possess a well-defined and highly tunable molecular structure and porosity, a large specific surface area, adjustable active sites, and efficient metal loading capacity, making them one of the most promising support materials for metal SACs.
[0004] Currently, researchers have achieved stable loading of metal single atoms on CTFs through strategies such as coordination anchoring, defect engineering, templates, and post-synthetic modification. However, practical applications still face challenges such as single-atom aggregation, limited loading capacity, uneven distribution, unclear catalytic mechanisms, and difficulty in precisely controlling the electronic structure of the metal center. These challenges severely hinder the application of CTF-based single-atom catalysts in fields such as energy catalysis and green chemistry. Therefore, it is necessary to develop new CTF-based catalysts to address these technical limitations. Summary of the Invention
[0005] In response to the above problems, in order to further improve the performance of CTFs catalysts, the present application provides a covalent triazine nanosheet loaded with metal atoms and a preparation method and application thereof.
[0006] The present application first provides a method for preparing covalent triazine nanosheets loaded with metal atoms, comprising the following steps:
[0007] 1) Mixing triazine monomer and carboxyl group-containing monomer, adding catalyst to react, grinding the obtained product and immersing it in alkali solution, then washing with solvent and drying to obtain CTF-COOH;
[0008] 2) mixing the CTF-COOH obtained in step 1) with water and grinding it, then washing and drying it to obtain CTF-COOH-NSs;
[0009] 3) Disperse the CTF-COOH-NSs obtained in step 2) into the loading liquid, immerse, react at room temperature, wash, and dry to obtain MCTF-R X The loading liquid contains the compound represented by formula I;
[0010] ;
[0011] The R X It is an electronic effector group.
[0012] Furthermore, it includes one or more of the following features:
[0013] 11) In step 1), the carboxyl group-containing monomer is 1,3,5-benzenetricarboxylic acid or 1,4-benzenedicarboxylic acid;
[0014] 12) In step 1), the catalyst is one of trifluoromethanesulfonic acid, ferric chloride, and aluminum chloride;
[0015] 13) In step 1), the solvent is one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran;
[0016] 14) In step 1), the ratio of the triazine monomer, the carboxyl group-containing monomer, and the catalyst is 10-200 mg: 10-200 mg: 10-200 μL;
[0017] 15) In step 1), the drying is carried out under vacuum at a temperature of 80-150°C for 6-12 hours;
[0018] 16) In step 1), the alkali solution is an ammonia solution.
[0019] Furthermore, in step 1), the triazine monomer and the carboxyl group-containing monomer are ground and mixed, a catalyst is added and placed in a quartz tube, which is then frozen with liquid nitrogen for 5-10 minutes, melted and sealed in a vacuum state, and kept at 150-350° C. for 0.5-15 hours.
[0020] Furthermore, in step 1), the temperature is raised to 150-350° C. at a heating rate of 4-6° C. / min, and then the reaction is kept at this temperature for 0.5-15 hours.
[0021] Furthermore, it includes one or more of the following features:
[0022] 21) In step 2), the CTF-COOH obtained in step 1) is ground with water for 1-4 hours, and the ratio of CTF-COOH to water is 20-150 mg:5-15 mL;
[0023] 22) In step 2), washing is performed with one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran;
[0024] 23) In step 2), the drying is freeze drying for 10-100 hours.
[0025] Furthermore, it includes one or more of the following features:
[0026] 31) In step 3), the loading solution comprises cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound represented by formula I;
[0027] 32) In step 3), in the compound represented by formula I, the R X Selected from H, substituted or unsubstituted amino, nitro, cyano, C1-C4 straight or branched chain alkyl, halogenated C1-C4 alkyl;
[0028] 33) In step 3), the drying is carried out under vacuum at a temperature of 80-150°C for 6-12 hours;
[0029] 34) In step 3), the immersion treatment is carried out under ultrasonic conditions for 25-35 minutes;
[0030] 35) In step 3), the heat preservation reaction is carried out at a temperature of 80-150° C. for 1-15 hours;
[0031] 36) In step 3), washing is performed with one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran;
[0032] 37) In step 3), the temperature of the reaction is raised to 80-150°C at a heating rate of 4-6°C / min, and then the temperature is kept for 1-15 hours.
[0033] Furthermore, in step 3), the usage ratio of cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound represented by formula I is 10-300 mg: 100-1000 μL: 1-200 mg.
[0034] Furthermore, in step 3), the compound represented by formula I is one or more of benzoic acid, p-nitrobenzoic acid, 4-(dimethylamino)benzoic acid, p-tert-butylbenzoic acid, p-toluic acid, and p-cyanobenzoic acid.
[0035] The present application provides a covalent triazine nanosheet loaded with metal atoms, which is prepared using the above-mentioned preparation method.
[0036] The present application also provides an application of covalent triazine nanosheets loaded with metal atoms, which is applied to the fields of oxygen reduction reaction, hydrogen evolution reaction, oxygen evolution reaction, nitrogen reduction reaction, and carbon dioxide reduction reaction.
[0037] Compared with the prior art, this application has the following beneficial effects:
[0038] 1. Compared with traditional catalyst materials or other single-atom catalysts, this application synthesizes highly crystalline, carboxyl-rich covalent triazine framework CTF-COOH-NSs nanosheets as a carrier. While ensuring the good stability of the catalyst, the rich carboxyl groups provide a guarantee for the good dispersion of metal atoms.
[0039] 2. Based on the covalent triazine framework CTF-COOH-NSs nanosheets as the carrier, the present application can effectively disperse the metal atoms evenly on the carrier, avoiding the problem of aggregation or agglomeration of metal atoms. This can greatly improve the utilization efficiency of metal atoms and ensure the uniform distribution of the active sites of metal atoms in the catalytic reaction, thereby significantly improving the catalytic performance.
[0040] 3. Traditional metal SACs have certain limitations in regulating the electronic structure of metal single atoms, making it difficult to achieve efficient and precise optimization. This application adopts small molecule coordination and utilizes groups with strong electronic effects carried by small molecules to further improve and regulate the electronic structure state of metal single atoms, effectively improving the catalytic activity of metal single atoms, especially in the field of electrocatalytic oxygen evolution. It shows better catalytic effect. In addition, the CTFs of this application have more excellent physical and chemical stability and can maintain relatively stable catalytic performance under more harsh reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1This is the PXRD pattern of CTF-COOH obtained in Preparation Example 2 of this application.
[0042] Figure 2 This is the FT-IR spectrum of CTF-COOH obtained in Preparation Example 2 of this application.
[0043] Figure 3 This is a TEM image of MCTF-R3 obtained in Example 3 of the present application.
[0044] Figure 4 This is the M-XPS pattern of MCTF-R3 obtained in Example 3 of the present application.
[0045] Figure 5 FT-IR spectra of MCTF-R1-MCTF-R4 obtained in Examples 1-4 of the present application.
[0046] Figure 6 These are the LSV diagrams of electrocatalytic oxygen evolution of MCTF-R1-MCTF-R4 obtained in Examples 1-4 of the present application.
[0047] Figure 7 Schematic diagram of the chemical structure of CTF-COOH prepared in this application.
[0048] Figure 8 MCTF-R prepared for this application X Schematic diagram of the chemical structure.
[0049] Figure 9 Schematic diagram of the metal atom ratio data of MCTF-R3 obtained in Example 3 of the present application after ICP measurement. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0051] After extensive experimental research, based on traditional SACs, single-atom catalysts, and traditional CTFs materials, this application has developed a method for preparing covalent triazine nanosheets loaded with metal atoms through technical iterations in multiple aspects such as synthesis route optimization and structural design, including the following steps:
[0052] 1) Mixing triazine monomer and carboxyl group-containing monomer, adding catalyst to react, grinding the obtained product and immersing it in alkali solution, then washing with solvent and drying to obtain CTF-COOH;
[0053] 2) mixing the CTF-COOH obtained in step 1) with water and grinding it, then washing and drying it to obtain CTF-COOH-NSs;
[0054] 3) Disperse the CTF-COOH-NSs obtained in step 2) into the loading liquid, immerse, react at room temperature, wash, and dry to obtain MCTF-R X The loading liquid contains the compound represented by formula I;
[0055] ;
[0056] The R X It is an electronic effector group.
[0057] Furthermore, it includes one or more of the following features:
[0058] 11) In step 1), the carboxyl group-containing monomer is 1,3,5-benzenetricarboxylic acid or 1,4-benzenedicarboxylic acid;
[0059] 12) In step 1), the catalyst is one of trifluoromethanesulfonic acid, ferric chloride, and aluminum chloride;
[0060] 13) In step 1), the solvent is one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran;
[0061] 14) In step 1), the ratio of the triazine monomer, the carboxyl group-containing monomer, and the catalyst is 10-200 mg: 10-200 mg: 10-200 μL;
[0062] 15) In step 1), the drying is carried out under vacuum at a temperature of 80-150°C for 6-12 hours;
[0063] 16) In step 1), the alkali solution is an ammonia solution.
[0064] In some specific embodiments of the present application, in step 1), the catalyst is one of trifluoromethanesulfonic acid, ferric chloride, and aluminum chloride. Typical, but non-limiting, examples include trifluoromethanesulfonic acid and ferric chloride. Generally, trifluoromethanesulfonic acid provides better experimental results.
[0065] In some specific embodiments of the present application, in step 1), the drying is carried out under vacuum, at a temperature of 80-150°C, and for a drying time of 6-12 hours. Specifically, the temperature can be 80-100°C, 100-120°C, or 120-150°C, and the drying time can be 6-8 hours, 8-10 hours, or 10-12 hours. Typically, but not limiting, the temperature is 80°C, 100°C, 120°C, or 150°C, and the drying time is 6 hours, 8 hours, 10 hours, or 12 hours. Under normal circumstances, in step 1), better experimental results can be achieved when the drying is carried out under vacuum, at a temperature of 120°C, and for a drying time of 12 hours.
[0066] In some specific embodiments of the present application, in step 1), the usage ratio of the triazine monomer, the carboxyl group-containing monomer and the catalyst can be 10-50 mg: 10-200 mg: 10-200 μL, 50-80 mg: 10-200 mg: 10-200 μL, 80-90 mg: 10-200 mg: 10-200 μL, 90-100 mg: 10-200 mg: 10-200 μL, 100-120 mg: 10-200 mg: 10-200 μL, 120-150 mg: 10 -200mg:10-200μL, 150-180mg:10-200mg:10-200μL, 180-200mg:10-200mg:10-200μL, 10-50mg:10-50mg:10-200 μL, 50-80mg: 50-70mg: 10-200μL, 50-90mg: 70-90mg: 10-200μL, 90-100mg: 90-100mg: 10-200μL, 100-120mg: 100-1 20mg: 10-200μL, 120-150mg: 120-140mg: 10-200μL, 150-180mg: 140-150mg: 10-200μL, 180-200mg: 150-180mg: 10 -200μL, 180-200mg: 180-200mg: 10-200μL, 10-50mg: 10-50mg: 10-40μL, 50-80mg: 50-70mg: 40-50μL, 50-90mg: 70 90 mg: 50-70 μL, 90-100 mg: 90-100 mg: 70-80 μL, 100-120 mg: 100-120 mg: 80-100 μL, 120-150 mg: 120-140 mg: 100-120 μL, 150-180 mg: 140-150 mg: 120-150 μL, 180-200 mg: 150-180 mg: 150-180 μL, 180-200 mg: 180-200 mg: 180-200 μL. Specifically, a typical but non-limiting example is that the ratio of the oxazine monomer, the carboxyl group-containing monomer, and the catalyst is 80-120 mg: 80-120 mg: 80-120 μL.
[0067] Furthermore, in step 1), the triazine monomer and the carboxyl group-containing monomer are ground and mixed, a catalyst is added and placed in a quartz tube, which is then frozen with liquid nitrogen for 5-10 minutes, melted and sealed in a vacuum state, and kept at 150-350° C. for 0.5-15 hours.
[0068] Furthermore, in step 1), the temperature is raised to 150-350° C. at a heating rate of 4-6° C. / min, and then the reaction is kept at this temperature for 0.5-15 hours.
[0069] In some specific embodiments of the present application, in step 1), the temperature is increased at a rate of 4°C / min, 5°C / min, or 6°C / min, and the temperature may be increased to 150-180°C, 180-200°C, 200-230°C, 230-250°C, 250-280°C, 280-300°C, 300-320°C, or 320-350°C. Specifically, under normal circumstances, in step 1), when the temperature is increased to 200°C at a rate of 5°C / min, the reaction is kept warm for 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, or 15 h, for example, 0.5 h.
[0070] Furthermore, it includes one or more of the following features:
[0071] 21) In step 2), the CTF-COOH obtained in step 1) is ground with water for 1-4 hours, and the ratio of CTF-COOH to water is 20-150 mg:5-15 mL;
[0072] 22) In step 2), washing is performed with one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran;
[0073] 23) In step 2), the drying is freeze drying for 10-100 hours.
[0074] In some specific embodiments of the present application, in step 2), the usage ratio of CTF-COOH to water can be 20-40 mg:5-15 mL, 40-60 mg:5-15 mL, 60-80 mg:5-15 mL, 80-90 mg:5-15 mL, 90-110 mg:5-15 mL, 110-120 mg:5-15 mL, 120-150 mg:5-15 mL, 20-40 mg:5-8 mL, 40-60 mg:8-10 mL, 60-80 mg:10-12 mL, 80-90 mg:12-13 mL, 90-110 mg:13-14 mL, and 110-120 mg:14-15 mL. Specifically, typically but not limitatively, in step 2), for example, the usage ratio of CTF-COOH to water is 80-120 mg:12-15 mL.
[0075] In some specific embodiments of the present application, in step 2), the drying is freeze-drying for 10-30 hours, 30-50 hours, 50-80 hours, or 80-100 hours. Specifically, the drying time is 10 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours, 70 hours, 80 hours, 90 hours, or 100 hours. Generally, freeze-drying for 48 hours in step 2) achieves optimal results.
[0076] Furthermore, it includes one or more of the following features:
[0077] 31) In step 3), the loading solution comprises cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound represented by formula I;
[0078] 32) In step 3), in the compound represented by formula I, the R X Selected from H, substituted or unsubstituted amino, nitro, cyano, C1-C4 straight or branched chain alkyl, halogenated C1-C4 alkyl;
[0079] 33) In step 3), the drying is carried out under vacuum at a temperature of 80-150°C for 6-12 hours;
[0080] 34) In step 3), the immersion treatment is carried out under ultrasonic conditions for 25-35 minutes;
[0081] 35) In step 3), the heat preservation reaction is carried out at a temperature of 80-150° C. for 1-15 hours;
[0082] 36) In step 3), washing is performed with one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran;
[0083] 37) In step 3), the heat preservation reaction is carried out by heating the temperature to 80-150°C at a heating rate of 4-6°C / min, and then heat preservation reaction is carried out for 1-15 hours.
[0084] As used herein, the term "alkyl" used alone or in combination may be linear or branched, and the number of carbon atoms may be, for example, C1-C4, C1-C3, C1-C2, etc. For example, alkyl includes, but is not limited to, methyl, ethyl, propyl, n-propyl, isopropyl, butyl, n-butyl, isobutyl, tert-butyl, sec-butyl, 1-methyl-butyl, 1-ethyl-butyl, pentyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 4-methyl-2-pentyl, 3,3-dimethylbutyl, 2-ethylbutyl, etc. In the present application, the "alkyl" is optionally substituted, and the substituted substituent is optionally selected from, for example, deuterium, hydroxyl, amino, thiol, halogen, cyano, nitro, carbonyl, ester, oxo, imide, phosphine oxide group, trifluoromethyl, trifluoromethoxy, C1-C3 alkyl, C1-C3 alkoxy and any combination thereof.
[0085] In some specific embodiments of the present application, in step 3), the drying is carried out under vacuum, at a temperature of 80-150°C, and for a drying time of 6-12 hours; specifically, the temperature can be 80-100°C, 100-120°C, or 120-150°C, and the drying time can be 6-8 hours, 8-10 hours, or 10-12 hours. Typically, but not limiting, the temperature is 80°C, 100°C, 120°C, or 150°C, and the drying time is 6 hours, 8 hours, 10 hours, or 12 hours. Under normal circumstances, in step 1), better experimental results can be achieved when the drying is carried out under vacuum, at a temperature of 120°C, and for a drying time of 12 hours.
[0086] In some specific embodiments of the present application, in step 3), for example, the insulation reaction is heated at a rate of 4°C / min, 5°C / min, or 6°C / min, and can be heated to 80-90°C, 90-100°C, 100-110°C, 110-120°C, 120-130°C, 130-140°C, or 140-150°C. Specifically, the insulation reaction is performed for 1-3 hours, 3-5 hours, 5-8 hours, 8-10 hours, 10-12 hours, or 12-15 hours. More specifically, the insulation reaction is performed for 8-12 hours. For example, the insulation reaction is performed for 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, or 15 hours.
[0087] Furthermore, in step 3), the usage ratio of cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound represented by formula I is 10-300 mg: 100-1000 μL: 1-200 mg.
[0088] Furthermore, in step 3), the compound represented by formula I is one or more of benzoic acid, p-nitrobenzoic acid, 4-(dimethylamino)benzoic acid, p-tert-butylbenzoic acid, p-toluic acid, and p-cyanobenzoic acid.
[0089] In some specific embodiments of the present application, in step 3), the usage ratio of cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound represented by formula I can be 10-30 mg: 100-1000 μL: 1-200 mg, 30-50 mg: 100-1000 μL: 1-200 mg, 50-70 mg: 100-1000 μL: 1-200 mg, 70-80 mg: 100-1000 μL: 1-200 mg, 80-90 mg: 100-1000 μL: 1-200 mg, 90-100 mg: 100-1000 μL: 1-200 mg, 100-110 mg: 100-1000 μL: 1-200 mg , 100-120mg: 100-1000μL: 1-200mg, 120-150mg: 100-1000μL: 1-200mg, 150-180mg: 100-1000μL: 1-200mg, 180-200mg: 100-1000μL: 1-200mg, 200- 230mg: 100-1000μL: 1-200mg, 230-250mg: 100-1000μL: 1-200mg, 250-280mg: 100-1000μL: 1-200mg, 280-300mg: 100-1000μL: 1-200mg, 10-30mg: 10 0-200μL: 1-200mg, 30-50mg: 200-300μL: 1-200mg, 50-70mg: 300-400μL: 1-200mg, 70-80mg: 400-500μL: 1-200mg, 80-90mg: 500-600μL: 1-200mg, 9 0-100mg: 600-700μL: 1-200mg, 100-110mg: 700-800μL: 1-200mg, 100-120mg: 800-900μL: 1-200mg, 120-150mg: 900-1000μL: 1-200mg, 10-30mg: 100 -200μL: 1-50mg, 30-50mg: 200-300μL: 50-80mg, 50-70mg: 300-400μL: 80-100mg, 70-80mg: 400-500μL: 100-120mg, 80-90mg: 500-600μL: 120-140m g, 90-100mg: 600-700μL: 140-150mg, 100-110mg: 700-800μL: 150-170mg, 100-120mg: 800-900μL: 170-185mg, 120-150mg: 900-1000μL: 185-200mg.
[0090] In the present application, more specifically, a method for preparing covalent triazine nanosheets loaded with metal atoms is provided, comprising the following steps:
[0091] 1) Add a certain amount of catalyst to a quartz glass tube 15-30 mm long and 5-10 mm in radius. Then, grind and mix the triazine-containing monomer and the carboxyl-containing monomer and add them to the tube. After freezing with liquid nitrogen, melt the mixture under vacuum and seal the tube. Finally, place the sealed tube in a muffle furnace at 150-350°C for 0.5-15 hours. After the reaction, open the tube at low temperature, grind the lumps, soak them in an ammonia solution overnight, and then wash them sequentially with deionized water, ethanol, N,N-dimethylformamide (DMF), and tetrahydrofuran (THF). After vacuum filtration, dry the mixture at 80-150°C for 12 hours to obtain CTF-COOH.
[0092] 2) adding water to the CTF-COOH obtained in step 1) and ball milling the mixture in a ball mill for 1-4 h. The product was washed with deionized water and vacuum filtered, and freeze-dried for 48 h to obtain CTF-COOH-NSs.
[0093] 3) The CTF-COOH-NSs obtained in step 2) were dispersed in the loading liquid and subjected to ultrasonic immersion treatment for 30 min. Finally, the sealed glass bottle was placed in a muffle furnace at 80-150°C for 1-15 h. The mixture was washed with deionized water and anhydrous ethanol and dried in vacuum at 80-150°C to obtain MCTF-R X The loading liquid comprises cobalt nitrate hexahydrate, 0.5M NaOH solution and the compound represented by formula Ⅰ;
[0094] ;
[0095] The R X It is an electronic effector group.
[0096] Preparation Example 1
[0097] The triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (80 mg) and the carboxyl group-containing monomer 1,4-phthalic acid (PTA) (120 mg) were ground and mixed, and added to a quartz glass tube containing the catalyst CF3SO3H (80 μL). After cooling in liquid nitrogen for 5 min, the quartz tube was flame-sealed under vacuum and transferred to a muffle furnace.
[0098] The muffle furnace was kept at 150°C for 30 min (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 min and then opened. The initial product of the reaction was collected by grinding. The initial product was ground and soaked in an ammonia solution overnight. It was washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone and tetrahydrofuran in sequence, and dried in a vacuum at 120°C for 12 h to obtain the crystalline product CTF-COOH.
[0099] Preparation Example 2
[0100] The triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (100 mg) and the carboxyl group-containing monomer 1,4-phthalic acid (PTA) (100 mg) were ground and mixed, and added to a quartz glass tube containing a catalyst CF3SO3H (100 μL). After cooling in liquid nitrogen for 5 min, the quartz tube was flame-sealed under vacuum and transferred to a muffle furnace.
[0101] The muffle furnace was kept at 200°C for 30 min (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 min and then opened. The initial product of the reaction was collected by grinding. The initial product was ground and soaked in an ammonia solution overnight. It was washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone and tetrahydrofuran in sequence, and dried in a vacuum at 120°C for 12 h to obtain the crystalline product CTF-COOH.
[0102] Preparation Example 3
[0103] The triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (120 mg) and the carboxyl group-containing monomer 1,4-phthalic acid (PTA) (80 mg) were ground and mixed, and added to a quartz glass tube containing the catalyst CF3SO3H (120 μL). After cooling in liquid nitrogen for 5 min, the quartz tube was flame-sealed under vacuum and transferred to a muffle furnace.
[0104] The muffle furnace was kept at 200°C for 30 min (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 min and then opened. The initial product of the reaction was collected by grinding. The initial product was ground and soaked in an ammonia solution overnight. It was washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone and tetrahydrofuran in sequence, and dried in a vacuum at 120°C for 12 h to obtain the crystalline product CTF-COOH.
[0105] Example 1
[0106] The preparation method of the covalent triazine nanosheets loaded with metal atoms in this embodiment comprises the following steps:
[0107] 1) Triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (100 mg) and carboxyl-containing monomer 1,4-phthalic acid (PTA) (100 mg) were ground and mixed, and added to a quartz glass tube containing catalyst CF3SO3H (100 μL). After cooling in liquid nitrogen for 5 minutes, the quartz tube was flame-sealed under vacuum and transferred to a muffle furnace.
[0108] The muffle furnace was kept at 200°C for 30 minutes (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 minutes and then opened. The initial product of the reaction was collected by grinding. The initial product was then soaked in an ammonia solution overnight and washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran in sequence. The product was dried in a vacuum at 120°C for 12 hours to obtain the crystalline product CTF-COOH.
[0109] 2) Add water (12 mL) to the CTF-COOH (80 mg) obtained in step 1) and ball mill for 1 h. The product was washed with deionized water and vacuum filtered. The product was freeze-dried for 48 h to obtain CTF-COOH-NSs.
[0110] 3) The CTF-COOH-NSs (80 mg) obtained in step 2) were dispersed in a glass bottle containing the loading solution and ultrasonically impregnated for 30 min. Finally, the sealed glass bottle was placed in a muffle furnace at 80°C for 12 h (heating rate 5°C / min), then washed with deionized water and anhydrous ethanol and dried in vacuo at 100°C to obtain MCTF-R1.
[0111] The loading liquid includes cobalt nitrate hexahydrate (120 mg), 0.5 M NaOH solution (200 μL), the compound represented by formula I (p-nitrobenzoic acid, 200 mg), and an organic solvent DMF (12 mL).
[0112] Example 2
[0113] The preparation method of the covalent triazine nanosheets loaded with metal atoms in this embodiment comprises the following steps:
[0114] 1) Triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (100 mg) and carboxyl-containing monomer 1,4-phthalic acid (PTA) (100 mg) were ground and mixed, and added to a quartz glass tube containing catalyst CF3SO3H (100 μL). After cooling in liquid nitrogen for 5 minutes, the quartz tube was flame-sealed under vacuum and transferred to a muffle furnace.
[0115] The muffle furnace was kept at 200°C for 30 minutes (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 minutes and then opened. The initial product of the reaction was collected by grinding. The initial product was then soaked in an ammonia solution overnight and washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran in sequence. The product was dried in a vacuum at 120°C for 12 hours to obtain the crystalline product CTF-COOH.
[0116] 2) Add water (15 mL) to the CTF-COOH (120 mg) obtained in step 1) and ball mill for 2 h. The product was washed with deionized water and vacuum filtered. After freeze-drying for 48 h, CTF-COOH-NSs were obtained.
[0117] 3) The CTF-COOH-NSs (120 mg) obtained in step 2) were dispersed in a glass bottle containing the loading solution and ultrasonically impregnated for 30 min. Finally, the sealed glass bottle was placed in a muffle furnace at 120°C for 10 h (heating rate 5°C / min), then washed with deionized water and anhydrous ethanol and dried in vacuo at 100°C to obtain MCTF-R2.
[0118] The loading solution includes cobalt nitrate hexahydrate (100 mg), 0.5 M NaOH solution (400 μL), the compound represented by formula I (benzoic acid, 1 mg), and an organic solvent DMF (8 mL).
[0119] Example 3
[0120] The preparation method of the covalent triazine nanosheets loaded with metal atoms in this embodiment comprises the following steps:
[0121] 1) The triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (100 mg) and the carboxyl group-containing monomer 1,4-phthalic acid (PTA) (min) were transferred to a muffle furnace after flame sealing the quartz tube under vacuum;
[0122] The muffle furnace was kept at 200°C for 30 minutes (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 minutes and then opened. The initial product of the reaction was collected by grinding. The initial product was then soaked in an ammonia solution overnight and washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran in sequence. The product was dried in a vacuum at 120°C for 12 hours to obtain the crystalline product CTF-COOH.
[0123] 2) Add water (13 mL) to the CTF-COOH (90 mg) obtained in step 1) and ball mill for 3 h. The product was washed with deionized water and vacuum filtered. It was freeze-dried for 48 h to obtain CTF-COOH-NSs.
[0124] 3) The CTF-COOH-NSs (90 mg) obtained in step 2) were dispersed in a glass bottle containing the loading solution and ultrasonically impregnated for 30 min. Finally, the sealed glass bottle was placed in a muffle furnace at 100°C for 8 h (heating rate 5°C / min), then washed with deionized water and anhydrous ethanol, and dried in vacuo at 100°C to obtain MCTF-R3.
[0125] The loading liquid includes cobalt nitrate hexahydrate (110 mg), 0.5 M NaOH solution (500 μL), the compound represented by formula I (p-dimethylaminobenzoic acid, 80 mg), and an organic solvent DMF (9 mL).
[0126] Example 4
[0127] The preparation method of the covalent triazine nanosheets loaded with metal atoms in this embodiment comprises the following steps:
[0128] 1) The triazine monomer 2,4,6-trichloro-1,3,5-triazine (TCT) (100 mg) and the carboxyl group-containing monomer 1,4-phthalic acid (PTA) (min) were transferred to a muffle furnace after flame sealing the quartz tube under vacuum;
[0129] The muffle furnace was kept at 200°C for 30 minutes (heating rate 5°C / min). After the reaction, the quartz tube was cooled with liquid nitrogen for 5 minutes and then opened. The initial product of the reaction was collected by grinding. The initial product was then soaked in an ammonia solution overnight and washed with deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran in sequence. The product was dried in a vacuum at 120°C for 12 hours to obtain the crystalline product CTF-COOH.
[0130] 2) Add water (14 mL) to the CTF-COOH (110 mg) obtained in step 1) and ball mill the mixture for 4 h. The product was washed with deionized water and vacuum filtered. The product was freeze-dried for 48 h to obtain CTF-COOH-NSs.
[0131] 3) The CTF-COOH-NSs (110 mg) obtained in step 2) were dispersed in a glass bottle containing the loading solution and ultrasonically impregnated for 30 min. Finally, the sealed glass bottle was placed in a muffle furnace at 110°C for 11 h (heating rate 5°C / min), then washed with deionized water and anhydrous ethanol, and dried in vacuo at 100°C to obtain MCTF-R4.
[0132] The loading liquid includes cobalt nitrate hexahydrate (150 mg), 0.5 M NaOH solution (600 μL), the compound represented by formula I (p-tert-butylbenzoic acid, 50 mg), and an organic solvent DMF (7 mL).
[0133] Performance testing
[0134] 1. MCTF-R1-MCTF-R4 (5 mg) and carbon nanotubes (5 mg) obtained in Examples 1-4 were uniformly ground for 30 min, added to a mixed solvent (DMF:Nafion = 490 μL:10 μL), and ultrasonicated for 30 min to form a uniform catalyst ink. 10 μL was drop-coated on the surface of an L-shaped disk electrode to test the electrocatalytic oxygen evolution performance. The results are as follows: Figure 6 As shown in Figure 2, it can be seen that MCTF-R4 (tert-butylbenzoic acid) only reaches 10 mA cm at an overpotential of 358 mV. -2 The current density of MCTF-R3 (4-(dimethylamino)benzoic acid) can reach 10 mA cm at an overpotential of 302 mV. -2 current density.
[0135] It can be seen that the present application, by uniformly loading metal atoms on covalent triazine nanosheets and introducing small molecules carrying functional groups, can regulate the electronic structure of metal atoms through electronic effects, change the energy barrier of its catalytic reaction, change the electron transfer process in the catalytic reaction, and regulate the electron cloud density around the metal atoms, thereby optimizing its electrocatalytic oxygen evolution performance.
[0136] 2. The CTF-COOH obtained in Preparation Example 2 was subjected to PXRD and FT-IR tests. The specific results are as follows: Figure 1 and Figure 2 The MCTF-R3 obtained in Example 3 was subjected to transmission electron microscopy and XPS testing, and the specific results are shown in FIG. Figure 3 and Figure 4 The infrared spectrum test of MCTF-R1-MCTF-R4 obtained in Examples 1-4 was performed, and the specific results are shown as follows: Figure 5 shown.
[0137] Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present invention.
Claims
1. A method for preparing covalent triazine nanosheets loaded with metal atoms, characterized in that: The steps include: 1) A triazine monomer and a carboxyl group-containing monomer are mixed, a catalyst is added for reaction, the resulting product is ground and then immersed in an alkaline solution, followed by washing with a solvent and drying to obtain CTF-COOH; the carboxyl group-containing monomer is 1,3,5-benzenetricarboxylic acid or 1,4-benzenedicarboxylic acid; 2) mixing the CTF-COOH obtained in step 1) with water and grinding it, then washing and drying it to obtain CTF-COOH-NSs; 3) Disperse the CTF-COOH-NSs obtained in step 2) into the loading liquid, immerse, react at room temperature, wash, and dry to obtain MCTF-R X The loading liquid includes cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound shown in formula I; ; The R X It is an electronic effector group.
2. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 1, wherein: Also includes one or more of the following characteristics: 11) In step 1), the catalyst is one of trifluoromethanesulfonic acid, ferric chloride, and aluminum chloride; 12) In step 1), the solvent is one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran; 13) In step 1), the ratio of the triazine monomer, the carboxyl group-containing monomer, and the catalyst is 10-200 mg: 10-200 mg: 10-200 μL; 14) In step 1), the drying is carried out under vacuum at a temperature of 80-150°C for 6-12 hours; 15) In step 1), the alkali solution is an ammonia solution; 16) In step 1), the triazine monomer is 2,4,6-trichloro-1,3,5-triazine.
3. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 2, wherein: In step 1), the triazine monomer and the carboxyl group-containing monomer are ground and mixed, a catalyst is added and placed in a quartz tube, the mixture is frozen with liquid nitrogen for 5-10 minutes, the quartz tube is melted and sealed under vacuum, and the mixture is kept at 150-350° C. for 0.5-15 hours.
4. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 3, wherein: In the step 1), the temperature is raised to 150-350° C. at a heating rate of 4-6° C. / min, and then kept warm for reaction for 0.5-15 hours.
5. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 1, wherein: Also includes one or more of the following characteristics: 21) In step 2), the CTF-COOH obtained in step 1) is ground with water for 1-4 hours, and the ratio of CTF-COOH to water is 20-150 mg:5-15 mL; 22) In step 2), washing is performed with one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran; 23) In step 2), the drying is freeze drying for 10-100 hours.
6. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 1, wherein: Also includes one or more of the following characteristics: 31) In step 3), in the compound represented by formula I, the R X Selected from H, substituted or unsubstituted amino, nitro, cyano, C1-C4 straight or branched chain alkyl, halogenated C1-C4 alkyl; 32) In step 3), the drying is carried out under vacuum at a temperature of 80-150°C for 6-12 hours; 33) In step 3), the immersion treatment is carried out under ultrasonic conditions for 25-35 minutes; 34) In step 3), the heat preservation reaction is carried out at a temperature of 80-150° C. for 1-15 hours; 35) In step 3), washing is performed with one or more of deionized water, anhydrous ethanol, N,N-dimethylformamide, acetone, and tetrahydrofuran; 36) In step 3), the temperature of the reaction is raised to 80-150°C at a heating rate of 4-6°C / min, and then the temperature is kept for 1-15 hours.
7. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 6, wherein: In step 3), the usage ratio of cobalt nitrate hexahydrate, sodium hydroxide solution, and the compound represented by formula I is 10-300 mg: 100-1000 μL: 1-200 mg.
8. The method for preparing metal atom-loaded covalent triazine nanosheets according to claim 6, wherein: In the step 3), the compound represented by formula I is one or more of benzoic acid, p-nitrobenzoic acid, 4-(dimethylamino)benzoic acid, p-tert-butylbenzoic acid, p-toluic acid, and p-cyanobenzoic acid.
9. A covalent triazine nanosheet loaded with metal atoms, characterized in that: The method is as described in any one of claims 1 to 8.
10. An application of covalent triazine nanosheets loaded with metal atoms, characterized in that: The metal atom-loaded covalent triazine nanosheets according to claim 9 are applied to the fields of oxygen reduction reaction, hydrogen evolution reaction, oxygen evolution reaction, nitrogen reduction reaction, and carbon dioxide reduction reaction.
Citation Information
Patent Citations
Internal oxygen type zinc-air battery charger baby
CN119921446A
Method for large-scale preparation of crystalline carboxyl-functionalized covalent triazine framework through Friedel-Crafts reaction
CN119930992A